The relationship between physical office environments on employees’ productivity in furniture industry at Melaka Tengah District / Nur Fadzillah Badrishah - Badrishah, Nur Fadzillah (Faculty of Business and Management, 2018)
This study empirically examines the influence of office environment towards employee’s productivity in furniture industry at Melaka Tengah district. This study based on primary data collected from one hundred and thirty six employees who are working in furniture industry at Melaka Tengah district. A structured questionnaire was used for data collection. The data was analyzed using Statistic Package for Social Sciences (SPSS) version 20.0. The data was analyzed using the correlation and multiple regression analysis. All the findings were tested at 0.01 significance. The findings of this study show that office environment is very vital in terms of increasing employee’s productivity. The findings of this study show that furniture and lighting give positive moderate relationship towards employee’s productivity. Meanwhile, the regression analysis shows that office environment play 22.8% towards employee productivity. Thus it is recommended to every organization to pay fully attention on office environment because this effort will increase the productivity of employee and can increase the marginal profit of the organization. In the future study, it was recommended to focus on other industry at Melaka Tengah district, a wider study should be conducted which consist larger population and other elements of office environments should be considered.